Interracial Marriage and Black Women’s Racial Identity: Polyrhythmic Voices and Realities in Adult Education - Joyce McNickles (Adult Education Research Conference, 2010)
This research study explored how Black women who are married to White men understood, experienced, and described their Black identity. Applications of womanism, Black women’s epistemology, racial identity theory, and constructivist grounded theory revealed Exogamous Black Identity as a dimension of racial identity.